The Interconnected Histories of the Syriac Churches in the Sixteenth Century - Parker, L (Cambridge University Press, 2021)
The various Syriac-using churches of the middle east have generally been understood as rivals to each other, due to their different doctrinal positions, with separate histories that can be studied in isolation. This article argues that doctrinal differences should not be given undue prominence, and that in the sixteenth century there was in reality considerable interaction between the different churches. Increased contacts with Catholicism in this period may have encouraged these interactions, particularly in Rome itself, but connections were already present within the Ottoman empire. These contacts had a significant effect on the churches’ historical development.